2014
DOI: 10.1002/art.38865
|View full text |Cite
|
Sign up to set email alerts
|

Folate Depletion and Increased Glutamation in Juvenile Idiopathic Arthritis Patients Treated With Methotrexate

Abstract: Objective Folates exist as a fluctuating pool of polyglutamated metabolites that may serve as a clinical marker of MTX activity. This study evaluates circulating folate content and folate polyglutamate distribution in Juvenile Idiopathic Arthritis (JIA) patients and in a cell culture model based on MTX exposure and folate supply. Methods Blood, plasma and red blood cell (RBC) measurements of MTX and folates were obtained from previously published data sets and additional sample analysis for JIA patients rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
26
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 40 publications
1
26
0
Order By: Relevance
“…In particular, several markers of pyrimidine and purine biosynthesis, including deoxyuridine monophosphate, 2‐deoxycytidine, 2‐deoxyuridine, and IMP may represent highly sensitive markers of MTX activity. These findings are consistent with previous studies that have found MTX treatment is associated with systemic depletion of circulating folates and corresponding dysregulation of intermediates of nucleotide metabolism …”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…In particular, several markers of pyrimidine and purine biosynthesis, including deoxyuridine monophosphate, 2‐deoxycytidine, 2‐deoxyuridine, and IMP may represent highly sensitive markers of MTX activity. These findings are consistent with previous studies that have found MTX treatment is associated with systemic depletion of circulating folates and corresponding dysregulation of intermediates of nucleotide metabolism …”
Section: Discussionsupporting
confidence: 93%
“…In this study, K562 cells under normal growth conditions were either left untreated (i.e., controls) or treated with MTX at a concentration of 1,000 nM for 24 hours. The concentration of 1,000 nM was chosen based on MTX peak concentrations in the treatment of RA, and to allow analysis utilizing a complimentary data set including targeted metabolic profiling of folates in K562 cells treated with MTX . Under these conditions, K562 cells are efficient at the uptake and polyglutamation of MTX, which is believed to be important in its pharmacological activity .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations